Bosnia and Herzegovina vs. Her Trading Partner from Southeast Europe - KURTOVIC, Safet Rasim; HALILI, Blerim; MAXHUNI, Nehat (Turkish Economic Review, 2017)
Abstract. It is well known that there is a strong relationship between real depreciation of the real exchange rate and the trade balance. Therefore, in this paper we investigated the presence of the J-curve between Bosnia and Herzegovina and seven leading trading partners in Southeast Europe. In the study we have used time series of disaggregated data from 1999 to 2015 and econometric techniques such as co-integration analysis, vector error correction, Johansen’s co-integration test, diagnostic tests and tests of stability. The results have shown that there is a co-integration and the presence of the phenomenon of J-curve in the case of Romania and Bulgaria, while this effect is absent in other countries. Keywords. Trade balance, J-curve, Exchange rate, Cointegration, Elasticity. JEL. F14, F31, F32.